Introductory patient communication training for medical physics graduate students: Pilot experience. Issue 1 (28th October 2021) - Padilla, Laura; Meleski, Whitney Burton; Dominick, Caitlin; Athing, Caroline; Jones, Cassidy L.; Burns, Dana; Cathers, Lauretta A.; Fields, Emma C.
Abstract: Despite medical physics becoming a more patient‐facing part of the radiation oncology team, medical physics graduate students have no training in patient communication. An introductory patient communication training for medical physics graduate students is presented here. This training exposes participants to foundational concepts and effective communication skills through a lecture and it allows them to apply these concepts through realistic simulated patient interactions. The training was conducted virtually, and eight students participated. The impact of the training was evaluated based on changes in both confidence and competence of the participants' patient communication skills. Participants were asked to fill out a survey to assess their confidence on communicating with patients before and after the training. They also underwent a simulated patient interaction pre‐ and postlecture. Their performance during these was evaluated by both the simulated patient actors and the participants themselves using a rubric. Each data set was paired and analyzed for significance using a Wilcoxon rank‐sum test with an alpha of 0.05. Participants reported significantly higher confidence in their feeling of preparedness to interact with patients (mean = 2.38 vs. 3.88, p = 0.008), comfort interacting independently (mean = 2.00 vs. 4.00, p = 0.002), comfort showing patients they are actively listening (mean = 3.50 vs. 4.50, p = 0.005), and confidence handling challenging patient interactions (mean = 1.88 vs. 3.38, p = 0.01), after the training. Their encounter scores, as evaluated by the simulated patient actors, significantly increased (mean = 77% vs. 91%, p = 0.022). Self‐evaluation scores increased, but not significantly (mean = 62% vs. 68%, p = 0.184). The difference between the simulated patient and self‐evaluation scores for the postinstruction encounter was statistically significant ( p = 0.0014). This patient communication training for medical physics graduate students is effective at increasing both the confidence and the competence of the participants in the subject. We propose that similar trainings be incorporated into medical physics graduate training programs prior to students entering into residency.